MANAJEMEN LABA DAN MOTIVASI MANAJEMEN - Sekar Mayangsari (Media Riset Akuntansi, Auditing & Informasi, 2001)
This article address about earnings management. Earnings management is a kind of accounting manipulations besides income smoothing and creative accounting. Accounts manipulations have been matter of research, discussion and, even, controversy in several countries such as United States, Canada, United Kingdom, even in Indonesia especially during crisis period.The objective of this paper is to elaborate a general framework for earnings management and the management's motivations Besides that this article address the fact that accounting academics often have very different perceptions of earnings management than do practitioners and regulators Practitioners and regulators often see earnings management as problematic and in the need of immediate remedial action. Academics unwilling to believe that earnings management rise problem. The end of article, I purposed for future research in earnings management.